Expanding the chemical diversity of M13 bacteriophage - Allen, Grace L.; Grahn, Ashley K.; Kourentzi, Katerina; Willson, Richard C.; Waldrop, Sean; Guo, Jiantao; Kay, Brian K. (Frontiers in Microbiology, 2022)
M13 bacteriophage are very stable nanoparticles that can be modified by chemical and genetic methods and used for library screening, diagnostics, and assembly of nanostructures. Its capsid proteins can be functionalized by a variety of chemical reactions without loss of particle integrity, allowing attachment of binding and reporting agents such as antibodies and enzymes. In addition, Genetic Code Expansion (GCE) permits the introduction of non-canonical amino acids (ncAAs) into displayed peptides and proteins. The incorporation of ncAAs into phage libraries has led to the discovery of high-affinity binders with low nanomolar dissociation constant (KD) values that can potentially serve as target enzyme inhibitors. This article reviews how bioconjugation and the incorporation of ncAAs during translation have expanded the chemistry of peptides and proteins displayed by M13 virions for a wide variety of purposes.